PERAMALAN RATA-RATA HARGA BERAS PADA TINGKAT PERDAGANGAN BESAR ATAU GROSIR INDONESIA DENGAN METODE SARIMA (SEASONAL ARIMA) - Dimas Ariq Fajari; Mochamad Fauzan Abyantara; Habibi Ardani Lingga (JURNAL AGRIBISNIS TERPADU, 2021)
Rice is one of the important elements in maintaining Indonesian food security, almost all Indonesians consume rice derived from rice. Therefore, it is very important to pay attention to the increase and decrease in the price of rice every month so that the price of rice can be maintained stable and does not burden the community. This study aims to find the best forecasting model for the average rice price at the Indonesian wholesale or wholesale trade level for July 2020 to June 2021 using the SARIMA (Seasonal Autoregressive Integrated Moving Average) method, where the data used in this study are Average data. Average Price of Rice at Indonesian Wholesaler or Wholesale Level from January 2010 to June 2020 sourced from the Indonesian Central Statistics Agency. From the results of the research that has been done, it is found that ARIMA (1, 1, 0) (0, 0, 3) 12 as the best model that produces an MSE of 10356.71. From the results of this study, it is hoped that the government can take a concrete step in maintaining the stability of rice prices as one of the main food commodities of the Indonesian people.